Compressive properties and fracture behaviours of Ti/Al interpenetrating phase composites with additive-manufactured triply periodic minimal surface porous structures - Li, Zhou; Mo, Haotian; Tian, Jiahao; Li, Junhao; Xia, Shiqi; Jia, Xianshi; Zhou, Libo; Lu, Yao (Springer, 2025)
The triply periodic minimal surfaces (TPMS) structure is regarded as a highly promising artificial design, but the performance of composites constructed using this structure remains unexplored. Two porosity levels of Ti/Al interpenetrating phase composites (IPCs) were fabricated by infiltrating ZL102-Al melt into additive-manufactured TC4-Ti scaffolds with the TPMS porous in this study. The combination of the two-phase alloys exhibits structural integrity at the interfacial region, as evidenced by microscopic surfaces observed in uncompressed IPCs. Quasi-static compression tests were performed to demonstrate that the Young’s modulus, yield stress and maximum compressive stress of IPCs exhibit significant enhancement when compared to the individual TPMS scaffolds, due to the supporting and strengthening effect of the filling phase. In the compression process of IPCs, defects emerge initially at the interface between the ZL102 phase and TC4 phase, triggering the fracture and slip of the ZL102 phase, eventually propagating to involve fracture in the TC4 phase. The deformation behaviours obtained from numerical simulation were combined to support these experimental phenomena. The results show that the corresponding stress concentration region is the central region of the spiral surface, the maximum stress concentration region of the ZL102 phase is the same as that of the TC4 phase, and the ZL102 phase effectively shares part of the loading. The Ti/Al IPCs achieve equivalent load-bearing capacity through a simplified interpenetration process and the utilisation of lighter materials.
Keywords: Additive manufacturing; Triply periodic minimal surface; Interpenetrating phase composites; Porous structure; Compressive properties; 40 Engineering; 4016 Materials Engineering; Materials; 4017 Mechanical engineering